Praktik Hutang Piutang Online pada Aplikasi Pinjaman Now Tinjauan Fatwa DSN MUI dan KHES - Annisa Firdausi Nuzula; Ahmad Junaidi; Luqman Hakim; Mahatir Muhamad Ihsan (Jurnal Antologi Hukum, 2022)
Qardh is a property that is lent or given by (the creditor) to someone in need (the debtor), intended to help the debtor, and he must return it with the same value and time that both parties have determined. There are several ways to carry out accounts payable, one of which is by using online media or online applications. The legality of an online loan is also required to have a permit and be registered with the Financial Services Authority (OJK). The "Loan Now" online application is an online platform in great demand by the public. However, its existence is still in doubt. Moreover, it contradicts the DSN MUI Fatwa Number 117/DSN-MUI/IX/2018 rules and the Compilation of Sharia Economic Law (KHES). This paper focuses on: 1) How is the analysis of the legality of the application on online accounts payable practices of the "Loan Now" application from the perspective of DSN MUI Fatwa 117/DSN-MUI/IX/2018 and Compilation of Sharia Economic Law (KHES), 2) How is the analysis of DSN Fatwa MUI 117/DSN-MUI/IX/2018 and Compilation of Sharia Economic Law (KHES) on profit margins in Debt and Receivable Practices in the "Loan Now" Application. This research library research uses library data collection methods, reads and records, and processes research materials. This study utilizes library sources to obtain research data. The results of this study can be concluded as follows: 1) The legality of the "Now Loan" online application does not meet the requirements of a legal online loan as stated in the Fatwa of the National Sharia Council Number 117/DSN-MUI/IX/2018 and the Compilation of Sharia Economic Law (KHES). 2) Setting the margin in the "Loan Now" application is not by the Fatwa of the National Sharia Council Number 117/DSN-MUI/IX/2018 and the Compilation of Sharia Economic Law because, firstly, there is an addition to a substantial principal fund. Secondly, there is a fine if it is late in repayment or past maturity. Qardh adalah harta yang dipinjamkan atau diberikan oleh (kreditur) kepada seseorang yang membutuhkan (debitur) yang dimaksudkan untuk membantu pihak debitur dan dia harus mengembalikan dengan nilai yang sama dan waktu yang sudah ditentukan kedua belah pihak. Ada beberapa cara untuk melakukan hutang piutang, salah satunya dengan menggunakan media online atau aplikasi online. Legalitas suatu pinjaman online juga diperlukan agar pinjaman online tersebut dapat mempunyai izin dan terdaftar di Otoritas Jasa Keuangan (OJK). Aplikasi online “Pinjaman Now” merupakan platform aplikasi online yang banyak diminati oleh masyarakat. Namun saat ini keberadaanya masih diragukan. Terlebih dalam praktiknya sangat terbalik dengan aturan yang ada di dalam Fatwa DSN MUI Nomor 117/DSN-MUI/IX/2018 dan Kompilasi Hukum Ekonomi Syariah (KHES). Tulisan ini berfokus pada: 1) Bagaimana analisis terhadap legalitas aplikasi pada praktik hutang piutang online aplikasi “Pinjaman Now” perspektif Fatwa DSN MUI 117/DSN-MUI/IX/2018 dan Kompilasi Hukum Ekonomi Syariah (KHES), 2) Bagaimana analisis Fatwa DSN MUI 117/DSN-MUI/IX/2018 dan Kompilasi Hukum Ekonomi Syariah (KHES) terhadap margin keuntungan dalam Praktik Hutang Piutang di Aplikasi “Pinjaman Now”. Penelitian library research ini menggunakan metode pengumpulan data pustaka, membaca dan mencatat serta mengolah bahan penelitiannya. Penelitian ini memanfaatkan sumber perpustakaan untuk memperoleh data penelitiannya. Hasil dari penelitian ini dapat disimpulkan sebagai berikut: 1) Legalitas aplikasi online “Pinjaman Now” tidak memenuhi syarat sebagai pinjaman online yang legal seperti yang tertuang dalam Fatwa Dewan Syariah Nasional Nomor 117/DSN-MUI/IX/2018 dan Kompilasi Hukum Ekonomi Syariah (KHES). 2) Penetapan margin pada aplikasi “Pinjaman Now” tidak sesuai dengan Fatwa Dewan Syariah Nasional Nomor 117/DSN-MUI/IX/2018 dan Kompilasi Hukum Ekonomi Syariah karena pertama adanya penambahan pada dana pokok yang sangat besar dan kedua adanya denda jika terlambat dalam pelunasan atau melewati jatuh tempo.